Peran dan Tantangan Sistem Informasi Manajemen Dalam Menjaga Keunggulan Kompetitif Organisasi - Dinda Puspita Sari; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Management Information Systems have the main purpose of being an organizer, provider and a means of realizing operational efficiency, the basis for decision making, service to consumers and innovation and product creation. Seeing the development of the times, SIM has a structured, neat and easier program design. The role of SIM is aimed at meeting better quality and competitiveness. In SIM, the fulfillment of consumer demand is very concerned which plays a major role in maintaining the organization's commercial advantage. This positive contribution that organizations get through management information systems makes the state thinner on how important this system is.